Parental Guidance for Gadget Use during Early Childhood - Naila Chasanah; Yuli Kurniawati Sugiyo Pranoto (Jurnal Pendidikan dan Pengajaran, 2023)
Excessive use of gadgets and lack of assistance and parental supervision have a negative impact on early childhood. This research is a qualitative type with a research design approach, namely a case study. The study involved 4 primary subjects with the characteristics of mothers of children in the age range of 5-6 years. The purpose of this study is to analyze the habitual activities of parents in providing assistance to children, efforts to form a communication relationship with children, to the impact on the use of gadgets. Data collection using the questionnaire method with google forms, interviews and documentation which are then analysed with a qualitative approach. The results show that parents play an important role in assistance starting from granting permission to use, monitoring, to providing a safe duration/time. This research found that parents are overwhelmed to fulfill the assistance authority due to various factors: (1) busy parents are overcome by giving gadgets to children; (2) limited knowledge of the introduction of safe gadgets; (3) the characteristics of children who are already comfortable with gadgets; (4) the belief that the need for gadgets is not a bad thing, but rather a single solution to various problems including child development (e.g. gadgets help increase the vocabulary of children with speech delays). Meanwhile, the lack of assistance from parents results in excessive use of gadgets. The implications of this research are used as readers' future views regarding the importance of assistance and supervision in the use of gadgets in early childhood.